PERSEPSI PERAN, KONSISTENSI PERAN, DAN KINERJA - Rizky Dermawan Soemanagara1 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
This paper describes the relationship between role perception, role consistency, andperformance. The role consistency is described as a commitment to expected behavior for a given position. The description of the idea of consistency is borrowed from time-consistency theory of economics